2013
DOI: 10.1103/physreve.88.022504
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation studies of 4-n-butyl-4-isothiocyanato-1,1-biphenyl

Abstract: Positron annihilation lifetime spectroscopy (PALS) measurements were performed between 93 and 293 K in order to study the supercooled smectic-E (Sm-E) phase of 4-n-butyl-4'-isothiocyanato-1,1'-biphenyl (4TCB), the ordered molecular crystal of 4TCB, and the phase transition between the Sm-E phase and the ordered molecular crystal of 4TCB. The phase transition was well reflected in the abrupt increase of the ortho-positronium (o-Ps) lifetime and intensity. The value of the o-Ps lifetime in the Sm-E liquid crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The intensity of this component is lower than 10% and increases to about 20% during the transition. A similar conclusion was drawn in the case of 4TCB crystal phase for which I 3 is even lower, i.e., it increases from 0% to 5% with temperature before the transition and then to 21% during the transition [28]. The value of  3 between 1.8 ns and 1.9 ns is in accordance with the size of the molecular vacancy for 4TCB crystal lattice.…”
Section: Positron Annihilation In Liquid Crystalssupporting
confidence: 80%
See 1 more Smart Citation
“…The intensity of this component is lower than 10% and increases to about 20% during the transition. A similar conclusion was drawn in the case of 4TCB crystal phase for which I 3 is even lower, i.e., it increases from 0% to 5% with temperature before the transition and then to 21% during the transition [28]. The value of  3 between 1.8 ns and 1.9 ns is in accordance with the size of the molecular vacancy for 4TCB crystal lattice.…”
Section: Positron Annihilation In Liquid Crystalssupporting
confidence: 80%
“…The SmE phase of nTBC have been extensively investigated and new models of the SmE lamellar structure with two types of sublayers consisting of aromatic cores and alkyl chains of molecules has been proposed [30,31]. This is connected to the previous reports concerning molten state of the alkyl chains in the SmE phase which has been confi rmed by thermodynamic, structural, and spectroscopic studies including PALS results [28,32,33]. Formation of Ps bubbles in mobile liquid-like regions of hydrophobic alkyl chains was also found for the racemic triple chain amphiphilic diol 1 that exhibits hexagonal columnar and cubic mesophases [34].…”
Section: Positron Annihilation In Liquid Crystalsmentioning
confidence: 69%
“…PAS (positron annihilation spectroscopy) is a sensitive method for detection of structural defects at the atomic scale such as vacancies, vacancy clusters, dislocations, and nanometer-scale voids [13,14]. The basis of this technique is positron-electron annihilation process.…”
Section: Pas Techniquementioning
confidence: 99%
“…7−9 It is especially true for glass-formers, where the phenomenon of the so-called cold crystallization (cc) occurs on heating a substance. 10−14 For low molecular organic materials, the cc (a process typical for polymers and called recrystallization) has been identified on heating after softening of glasses of isotropic phases, 12−14 nematics, 7,15,16 crystal-like smectics, [7][8][9][10]17 conformationally disordered crystalline phases, 10,18 and ferroelectric phases 9,19 of liquid crystalline materials and also of plastic phases of alcohols. 20,21 In many cases, a metastable crystal is formed (one or more) which transforms on further heating to the stable crystalline phase.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies of phase transitions in liquid crystalline materials revealed complex polymorphism of liquid-like and solid-like phases. It is especially true for glass-formers, where the phenomenon of the so-called cold crystallization (cc) occurs on heating a substance. For low molecular organic materials, the cc (a process typical for polymers and called recrystallization) has been identified on heating after softening of glasses of isotropic phases, nematics, ,, crystal-like smectics, , conformationally disordered crystalline phases, , and ferroelectric phases , of liquid crystalline materials and also of plastic phases of alcohols. , In many cases, a metastable crystal is formed (one or more) which transforms on further heating to the stable crystalline phase. Research on the kinetics of cold-crystallization in liquid crystalline glass-formers was conducted by polarizing microscopy (POM) along with calorimetric (adiabatic and/or DSC) methods ,, and broadband dielectric spectroscopy (BDS), also performed in real time of the experiment. ,,, …”
Section: Introductionmentioning
confidence: 99%